An example of rich, real and multivariate survey data for use in school - Podworny, Susanne; Fleischer, Yannik; Stroop, Dietlinde; Biehler, Rolf

Lydia Böttger (Universität Paderborn) rezensiert: Michalak, Magdalena; Döll, Marion (Hrsg.) (2021): Lehrwerke und Lehrmaterialien im Kontext des Deutschen als Zweitsprache und der sprachlichen Bildung. [Deutsch als Zweitsprache Positionen, Perspektiven, Potenziale, Bd. 2]. Münster, New York: Waxmann, 164 Seiten. ISBN 978-3-8309-4105-7. - Böttger, Lydia (www.daz-portal.de)

Investigation into Target Speaking Rate Adaptation for Voice Conversion - Kuhlmann, Michael; Seebauer, Fritz; Ebbers, Janek; Wagner, Petra; Haeb-Umbach, Reinhold (Interspeech 2022)

Schorsch Kamerun: „Extra Vages machen wir aus tiefer Überzeugung“. - Jacke, Christoph (Kaput. Magazin für Insolvenz & Pop.)

Effective vocabulary learning apps: what should they look like? An evaluation with a particular view to German language acquisition - Lentfort, Theresa; Künzl-Snodgrass, Annemarie; de Vincent-Humphreys, Maren (Ab Initio Language Teaching in British Higher Education. The Case of German)

Informed vs. Blind Beamforming in Ad-Hoc Acoustic Sensor Networks for Meeting Transcription - Gburrek, Tobias; Schmalenstroeer, Joerg; Heitkaemper, Jens; Haeb-Umbach, Reinhold (2022 International Workshop on Acoustic Signal Enhancement (IWAENC))

A Meeting Transcription System for an Ad-Hoc Acoustic Sensor Network - Gburrek, Tobias; Boeddeker, Christoph; von Neumann, Thilo; Cord-Landwehr, Tobias; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold

Threshold Independent Evaluation of Sound Event Detection Scores - Ebbers, Janek; Haeb-Umbach, Reinhold; Serizel, Romain (Proceedings of the IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
Performing an adequate evaluation of sound event detection (SED) systems is far from trivial and is still subject to ongoing research. The recently proposed polyphonic sound detection (PSD)-receiver operating characteristic (ROC) and PSD score (PSDS) make an important step into the direction of an evaluation of SED systems which is independent from a certain decision threshold. This allows to obtain a more complete picture of the overall system behavior which is less biased by threshold tuning. Yet, the PSD-ROC is currently only approximated using a finite set of thresholds. The choice of the thresholds used in approximation, however, can have a severe impact on the resulting PSDS. In this paper we propose a method which allows for computing system performance on an evaluation set for all possible thresholds jointly, enabling accurate computation not only of the PSD-ROC and PSDS but also of other collar-based and intersection-based performance curves. It further allows to select the threshold which best fulfills the requirements of a given application. Source code is publicly available in our SED evaluation package sed_scores_eval.

KI im Einsatz. Interdisziplinäre Herausforderungen im Projekt UAV-Rescue - Philippi, Martina; Heusinger-Heß, Victoria; Ari, Meral; Krüger, Emily (Mensch und Computer 2022 - Workshopband)
Im Projekt „UAV-Rescue: UAV-getragene Sensorik zur KI-basierten Unterstützung von Rettungsmissionen“ wird an einem unbemannt fliegenden System geforscht, das in schwer zugänglichen Räumen bei der Rettungspriorisierung hilft, indem es den Einsatzkräften eine Visualisierung des Raumes mit darin lokalisierten Lebenszeichen zur Verfügung stellt. Diese neue Technologie wirft verschiedene ethische Fragestellungen auf, die unter anderem die Nutzung von Künstlicher Intelligenz zur Lebenszeichendetektion und die Einbettung der neuen Technologie in die Einsatzpraxis betreffen. Die ethische Begleitforschung des Projekts adressiert diese Fragestellungen in einem interdisziplinären und iterativen Diskurs mit Technikpartnern und Endanwendern. Einige dieser Fragestellungen werden hier vor dem Hintergrund der eingesetzten KI-Methoden und der bestehenden Einsatzpraxis beim THW vorgestellt.
Keywords: rescue robotics; interdisciplinarity; artifical intelligence; ethics

Same Different but not Same Same: Ethnic Discrimination in Application Procedures in the German Public Sector - Auer, Thorsten Fabian; Ekemen, Helin; Hagedorn, Carolin; Heise, Chantal; Rese, Christine (Empirical Economics Letters)
Regulations to prevent ethnic discrimination in accessing the labor market are implemented most thoroughly in the public sector. However, it remains to be assessed if these regulations are internalized. We conducted a field experiment to examine ethnic discrimination when applying for internships in German municipalities by unsolicited inquiries. We compared responses in German cities to Turkish, Italian, and German applicants in two periods, and find consistent disadvantages for the Turkish and Italian applicants as well as differences related to gender. Thus, the likelihood for ethnic discrimination rises when applying for positions in public institutions that are not subject to regulations.
Keywords: Ethnic Discrimination; Public Sector; Field Experiment; Application Procedure